Attitudes on Cashless Society of Undergraduate Students in Trang Province - Leekpai, Pradthana (Journal of Human and Society, Sisaket Rajabhat University, 2022)
This research aimed to study the attitudes on cashless society of undergraduate students in Trang Province and to compare these attitudes with their personal factors. In total, 390 undergraduate students in Trang Province were recruited in this study. A questionnaire was the instrument for data collection. The statistics used for data analysis were frequency, percentage, mean, standard deviation, t-test, and One-Way ANOVA. The results revealed that the overall attitude towards the cashless society among undergraduate students in Trang Province were at a high level. In addition, the attitudes about the cashless society on the compatibility factor were rated as the highest, followed by the attitudes about the usefulness and the ease of use factor, and the attitudes about the costs factor respectively. The undergraduate students in Trang Province with differences in ages, average grades, and money received from parents per month had different attitudes towards the cashless society at the statistically significant level of 0.05.